Non-invasive of liver fibrosis diagnostics: the role of serum markers - A. F. Sheptulina; Ye. N. Shirokova; V. T. Ivashkin (Российский журнал гастроэнтерологии, гепатологии, колопроктологии)
Aim of review. The prognosis and management approach for chronic liver diseases of any etiology in many respects are determined by stage and extent of fibrosis which reflects activity, spread and duration of liver disease. Aim of current publication was to highlight these issues.Summary. Investigations in the field of fibrogenesis processes made possible quantitative estimation of liver fibrosis by non-invasive tests based both on assessment of peripheral blood levels of substances, directly involved in various stages of extracellular matrix synthesis and disintegration, and on the routine laboratory tests reflecting activity of inflammation, degree of disorder of synthetic liver function and fibrosis progression.Conclusion. Study of diagnostic accuracy of serum markers for assessment of fibrosis stage in liver disea ses of various etiology will provide development of comprehensive non-invasive test for estimation of treatment response rate, course and progression rate of disease